CHILDREN'S CONCEPTUAL FRAMEWORK ABOUT NATURAL PHENOMENA AND ITS IMPLICATION FOR SCIENCE TEACHING - Mukhopadhyay, Dilip Kumar (SCHOOL SCIENCE, 2013)
By appreciating, amongst other things, the perceptions that the learner brings to the class, the teacher can reduce the discrepancies between pupil’s intentions and his learning. Similarity of constructed meaning to that intended by the teacher depends on the way a pupil copes with the language used by the teacher during instruction